Safety in Numbers: Downsizing and the Deinstitutionalization of Permanent Employment in Japan - Ahmadjian, Christina L.; Robinson, Patricia (Administrative Science Quarterly, 2001)
This study examines the role of downsizing in the deinstitutionalization of permanent employment among publicly listed companies in Japan between 1990 and 1997. We found that although economic pressure triggered downsizing, social and institutional pressures shaped the pace and process by which downsizing spread. Large, old, wholly domestically owned, and high-reputation Japanese firms were resistant to downsizing at first, as were firms with high levels of human capital, as reflected by high wages, but these social and institutional pressures diminished as downsizing spread across the population. We argue that this breakdown of social constraints was due to a safety-in-numbers effect: as downsizing became more prominent, the actions of any single firm were less likely to be noticed and criticized, and the effect of the institutional factors that once constrained downsizing diminished.